Perceived parenting style and suicidal/Non-suicidal self-Injury in students at the University of Cape Town - Chundu, Mwanja (Department of Psychiatry and Mental Health, 2021)
Background: Low- and middle-income countries like South Africa carry the greatest suicide burden, with local general population suicide attempt rates of 2.9–22.7%, in comparison to 0.7–9% in international literature. Non-suicidal self-injury (NSSI) commonly co-occurs with suicidal behaviours and estimates range from 5.5% internationally to 19.4% in South Africa. As a subgroup of the general population, university students are at higher risk both of suicidal behaviours and NSSI (S/NSSI). Risk factors for S/NSSI include parenting style; however, very little is known about the relationship between parenting styles and S/NSSI in university students in the South African context. Objectives: In this dissertation we set out to perform a literature review relating to explanatory models and risk factors associated with S/NSSI and then proceeded to collect novel data from students at the University of Cape Town. This research study aimed to describe the rates of S/NSSI behaviours and to explore the relationship between the Baumrind parenting style typography and S/NSSI in university students. The study hypothesised that authoritative parenting would negatively correlate with S/NSSI. No a priori hypotheses were made about the other parenting styles investigated. Methods: In chapter 1, we performed a literature review of peer-reviewed publications on Pubmed, Psychinfo via EBSCOHost and MEDLINE via EBSCOHost identified through search terms that were relevant to the focus of the study. In chapter 2 novel data were collected. Students from all faculties at the University of Cape Town were invited to complete an anonymous, online electronic survey. Data collection included a socio-demographic questionnaire, Parenting Styles and Dimensions Questionnaire and Self-Harming Behaviours Questionnaire. Descriptive statistics quantified parenting styles, suicidal behaviours and NSSI. Spearman's correlation coefficients examined the association between parenting style and S/NSSI. Results: Literature review provided a topline review of explanatory models and risk factors associated with S/NSSI and identified relevant literature about parenting styles using the Baumrind typology. In the electronic survey of university students, the rate of suicidal attempts was 6.3% and of NSSI was 22.7%. Suicide threats, suicidal thoughts, and thoughts of dying were reported by 5.9%, 35.7% and 50.7% respectively. No significant differences were seen between male and female students. We observed no significant association between authoritative parenting and suicidal behaviours, but authoritative mothers and fathers were significantly associated with a history of NSSI. Both permissive mothers and fathers were associated with suicide attempts, threats, and thoughts, whereas only permissive mothers were associated with NSSI. Conclusion: This study replicated previously reported high rates of S/NSSI in South African university students in comparison to general population and international data. Contrary to our hypothesis, authoritative parenting style was positively correlated with NSSI, but not with suicidal behaviours. Further studies are warranted to examine parenting style, and permissive parenting, in particular, in relation to S/NSSI